PENGARUH METODE PERMAINAN BERBASIS ANDROID TERHADAP PENGENALAN NAMA-NAMA SURAT PENDEK DALAM AL-QURAN DI MADRASAH IBTIDAIYAH - Nadlir, Nadlir; Ainaul Mardhiyah, Ainaul; Aji, Putri Cintya Melani (STIT AL MULTAZAM, 2024)
In the digital era, technological transformation has occurred in various aspects, one of which is the world of education. The minimal availability of digital learning media, especially in learning the Koran and Hadith, the information in textbooks does not attract students' interest in reading. This needs to be overcome by innovating digital-based learning media to make it easier for students to receive information and knowledge. One of the innovations in digital-based learning media is MARISUQUR. The aim of this research is to create and analyze the effectiveness of the MARISUQUR game on the knowledge and skills of MI/SD level students in recognizing the names of Al-Quran letters in juz 30. This research uses quantitative methods with a pre-test and post-test design. Data collection was carried out through: observation, interviews and tests on 30 students of MI Nurul Ulum Jogodalu Benjeng Gresik. Data analysis uses paired sample t-test statistical measurements. The results of the research show that the significance value is 0.000 0.05, so it is concluded that the application of the MARISUQUR game is significantly effective in attracting students' interest and increasing their ability to compose words correctly, especially regarding recognizing the names of Al-Quran letters in juz 30. Method This also has an impact on increasing activity, interest and motivation towards learning Al-Qur'an Hadith at MI. This is because the Android-based game method can attract interest and increase student learning activities.